2018
DOI: 10.1155/2018/1895208
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Elastic and Viscoelastic Material Parameters by Means of a Tikhonov Regularization

Abstract: For studying the interaction of displacements, stresses, and acting forces for elastic and viscoelastic materials, it is of utmost importance to have a decent mathematical model available. Usually such a model consists of a coupled set of nonlinear differential equations together with appropriate boundary conditions. However, since the different material classes vary significantly with respect to their physical and mechanical behavior, the parameters which appear in these equations are unknown and therefore ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…In particular, the Maxwell element with the smallest relaxation time (here: (µ 1 , τ 1 )) is most affected. This confirms stability investigations obtained in [8].…”
Section: Perturbed Datasupporting
confidence: 91%
See 2 more Smart Citations
“…In particular, the Maxwell element with the smallest relaxation time (here: (µ 1 , τ 1 )) is most affected. This confirms stability investigations obtained in [8].…”
Section: Perturbed Datasupporting
confidence: 91%
“…However, it is obvious that the reconstructions of (µ 1 , τ 1 ) show a tremendous error, while the other parameters are computed rather stably. This confirms considerations of the authors in [8] where the authors have proven that the reconstruction of small relaxation times always is severely ill-conditioned and the condition We repeat this experiment with 100 different perturbed data sets with the same noise level and plot the values of (µ 1 , τ 1 ) in Figure 6.1. We see that there is a very large variance in values spread over 100 different experiments.…”
Section: Perturbed Datasupporting
confidence: 82%
See 1 more Smart Citation
“…Park and Schapery [ 23 ] used the Prony series to describe the relaxation and creep behavior of a viscoelastic material. Diebels et al [ 24 ] identified the elastic and viscoelastic material parameters from constitutive equations by means of a Tikhonov regularization and inspired an extra penalty term from the stress-strain relationships to expect better results. Haupt et al [ 25 ] used a relatively simple identification method based on the concept of fractional calculus and obtain the model-inherent material parameters.…”
Section: Introductionmentioning
confidence: 99%